Poverty Alleviation in a Financial Programming Framework : An Integrated Approach - Chand, Sheetal; Shome, Parthasarathi (Washington, D.C. : International Monetary Fund, 1995)
Poverty alleviation is typically addressed in financial programming through additive programs that target vulnerable groups but without modifying the underlying stabilization and adjustment targets. Instead, this paper integrates the poverty alleviation objective into the financial programming framework using a well-known poverty index. In consequence, the assessment of trade-offs between competing objectives is facilitated. A simulation demonstrates how the integrated approach can reduce adverse effects on poverty and improve the balance of payments, although at the cost, temporarily, of a higher fiscal deficit and inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet